Advances in the development of imaging probes and aggregation inhibitors for alpha-synuclein - Xu Ming-ming; Ryan Philip; Rudrawar Santosh; Quinn Ronald J; Zhang Hai-yan; Mellick George D (Acta Pharmacologica Sinica, 2020)
Abnormal protein aggregation has been linked to many neurodegenerative diseases, including Parkinson’s disease (PD). The main pathological hallmark of PD is the formation of Lewy bodies (LBs) and Lewy neurites, both of which contain the presynaptic protein alpha-synuclein (α-syn). Under normal conditions, native α-syn exists in a soluble unfolded state but undergoes misfolding and aggregation into toxic aggregates under pathological conditions. Toxic α-syn species, especially oligomers, can cause oxidative stress, membrane penetration, synaptic and mitochondrial dysfunction, as well as other damage, leading to neuronal death and eventually neurodegeneration. Early diagnosis and treatments targeting PD pathogenesis are urgently needed. Given its critical role in PD, α-syn is an attractive target for the development of both diagnostic tools and effective therapeutics. This review summarizes the progress toward discovering imaging probes and aggregation inhibitors for α-syn. Relevant strategies and techniques in the discovery of α-syn-targeted drugs are also discussed.